2021
DOI: 10.3390/antiox10091449
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Regulates the Immunity, Anti-Oxidation and Apoptosis in Abalone Haliotis discus hannai Ino

Abstract: The present study was conducted to investigate the roles of ascorbic acid (AA) in immune response, anti-oxidation and apoptosis in abalone (Haliotis discus hannai Ino). Seven semi-purified diets with graded levels of AA (0, 50, 100, 200, 500, 1000 and 5000 mg/kg) were fed to abalone (initial weight: 12.01 ± 0.001 g, initial shell length: 48.44 ± 0.069 mm) for 100 days. The survival, weight gain rate and daily increment in shell length were not affected by dietary AA. The AA content in the gill, muscle and dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 103 publications
(128 reference statements)
3
7
0
Order By: Relevance
“…The values of these parameters in the present study for Endo vit. C treatment was comparable with other studies, i.e., Lin & Shiau (2004) in grouper, Epinephelus malabaricus, Naggar & Lovell (1991) (Wang et al, 2003), as a result it must therefore be supplied via the feed at recommended dosages for active uptake (Trichet et al, 2015;Omoniyi & Ovie, 2018;Luo et al, 2021). The digestive physiology was affected by infeed probiotics (Thepax) through improvement of intestinal enzyme activitiesa and significant increase in at least 11% in intestinal lactic acid bacteria population was observed (Adel et al, 2016).…”
Section: Discussionsupporting
confidence: 75%
“…The values of these parameters in the present study for Endo vit. C treatment was comparable with other studies, i.e., Lin & Shiau (2004) in grouper, Epinephelus malabaricus, Naggar & Lovell (1991) (Wang et al, 2003), as a result it must therefore be supplied via the feed at recommended dosages for active uptake (Trichet et al, 2015;Omoniyi & Ovie, 2018;Luo et al, 2021). The digestive physiology was affected by infeed probiotics (Thepax) through improvement of intestinal enzyme activitiesa and significant increase in at least 11% in intestinal lactic acid bacteria population was observed (Adel et al, 2016).…”
Section: Discussionsupporting
confidence: 75%
“…In addition, VC also promoted the expression of caspase-3, caspase-7, and caspase-9 and aggravated the apoptosis of grass carp (Ctenopharyngodon idella) cells [20]. It has been reported that VC can improve the antioxidant, antiapoptotic, and immune abilities of the abalone Haliotis discus hannai Ino [21].…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed a significant decrease in both serum iron level and serum TIBC in all ISMN treated groups in a concentration-dependent manner. This result can be explained by the increased serum nitric oxide by the increased ISMN dose and by the induced oxidative stress decreasing the serum iron and TIBC ( Luo et al, 2021 ). It has been reported that iron deficiency anemia increases through NO production, and elevated NO concentrations in iron deficiency anemia.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, an improvement in the serum iron level and TIBC was observed by the effect of l -ascorbic acid. This improvement may be due to the beneficial effect of l -ascorbic acid to enhance iron absorption ( Tang et al, 2021 , Luo et al, 2021 ). In our study, all groups treated with ISMN showed a significant increase in serum nitric oxide concentrations.…”
Section: Discussionmentioning
confidence: 99%